Poetics of Islamic Historiography : Deconstructing Ṭabarī's History - Shoshan, Boaz (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
Offering a new approach to the study of Ṭabarī's History , the most comprehensive historical work written by a classical Muslim historian, this book applies concepts developed by critical theorists and suggests a reading of historiographical material that is not primarily concerned with reconstructing the facts. The book consists of two parts. Part one exposes the assumptions involved in writing classical Islamic history, especially the mimetic aspiration of the sources and the practice that subverts it. Part two examines in detail four significant events in the history of early Islam and demonstrates how a deconstructionist reading subjects endows these with a considerably different meaning and subjects them to new light.